Análise, estudo e simulação de linhas de transmissão de microfita - Souto, Gabriel Amaral (Universidade Federal Rural do Semi-Árido, 2018)
This study brings a analitical approach of applied eletromagnetism on microstrip lines. Through the basic principles of eletromagnetism, using the Maxwell equations and the Helmholtz equation, taken its solucions applied on the patch line with only one dieletric and analyse it’s transversal and propagating fields. In conclusion, the impedance matrix is used to calculate the parameters and patterns that can be found on the propagating field for a given operation frequency.
Artigo Acadêmico
Keywords: Linha de microfita; Eletromagnetismo aplicado; Campos propagantes; ENGENHARIAS::ENGENHARIA ELETRICA